The illustrated encyclopedia of Islamic art and architecture : a comprehensive history of Islam's 1400-year legacy of art and design, with 500 photographs, reproductions and fine-art paintings - Chapman, Caroline (Illustrated encyclopedia, 2010)
Provides an in-depth survey of 1,400 years of art and architecture from ornate mosques and pottery, to calligraphy, carpets and costume. This book discusses how wonderful works of sacred art glorified Islam's message. It explores the rich heritage of Islamic art